LIFE AND ITS VALUE IN THE CHRISTIAN PERSPECTIVE - Nereparampil, Lucius (Journal of Dharma, 1996)
Life is precious to all of us. We can notice in this world various levels of life, and in each level a natural tendency among all the living beings to preserve life. If we look into the attitude of human beings towards life from the stone-age upto now, we may come across a wide variety of customs and beliefs. Even the well known world-religions do not have a unified view on this matter. The christian sacred writings, however, contain a view of life which is perhaps the most valuable contribution of the past humanity to the modern world. We shall now explore this christian view of life shining out of the pages of the Bible.